Development of Guided-Inquiry-Oriented Electronic Student Worksheet to Improve Critical Thinking Ability on Acid-Base Material - Sarafina, Intan; Nasrudin, Harun (Universitas Syiah Kuala, 2024)
Critical thinking abilities are needed in the 21st-century, whichcan be improved by learning chemistry, one of which is acid-basematerial and use relevant electronic teaching materials. This studyaims to produce guided-inquiry-oriented e-worksheet that useliveworksheet to improve students' critical thinking ability interms of validity, practicality, and effectiveness. The type ofresearch used is the 4D model development by Thiagarajan, butonly up to the third stage. We limited the investigation to 32students at State Senior High School 21 of Surabaya. Thevalidation results indicate that the electronic worksheet achieves acontent and construct validity score of five in a very validcategory. The practicality of electronic worksheet can be seenfrom the results of the student response questionnaire with apercentage of 98% with very practical category and got apercentage of 97% on the results of observations of studentactivity per meeting with a very practical category. The results ofthe effectiveness of the electronic worksheet in terms of theoverall n-gain value got a value with a high category supportedby the sig value. (two-sided) obtained from the paired sample t-test of .001. Based on these results, it can be concluded that theelectronic worksheet using liveworksheet is feasible to use asteaching material to improve students' critical thinking abilities.